Experimental Study on Ultrasonic Vibration-Assisted Grinding of SiCp/Al Composites Grinding - Jinghao Jin; Jian Mao; Rong Wang; Mengyang Cui (Micromachines)
Aluminum matrix composites reinforced with silicon carbide particles (SiCp/Al) are widely used in aerospace fields with excellent properties, such as high specific strength, high specific stiffness, and high thermal conductivity. Due to the heterogeneous structure, its microstructure is one of the determinants of workpiece life, and ultrasonic vibration can improve the surface quality after grinding. Therefore, in this study, ultrasonic vibration-assisted grinding (UVAG) orthogonal tests were designed to study the surface morphology of SiCp/Al and the form of SiC particle removal under different machining parameters based on the SEM observation of the material surface, and to analyze the percentage of different kinds of grinding forces. The results show that the existence of particle fracture force depends on the relative sizes of the maximum undeformed chip thickness and the critical chip thickness. Through surface roughness testing and analysis, the influence of processing parameters on the surface roughness of the material is explored, and it is found that the application of ultrasound reduces the surface roughness of the material, which can be used as a guideline for the surface quality of the grinding process and the optimization of the process parameters.